THE EFFECT OF APPLYING THE PRINCIPLES OF LEADERSHIP, EMPLOYEE INVOLVEMENT, AND CONTINUOUS IMPROVEMENT ON EMPLOYEE JOB SATISFACTION - Prasanti, Aderia Putri; Damayanti, Nyoman Anita (Jurnal Administrasi Kesehatan Indonesia, 2015)
ABSTRACTÂ Job satisfaction rate of Rumah Sakit Mata Undaan Surabaya (RSMU)âs employees increasedfrom 76,92% to 78,92% in 2012-2013. Unfortunately, in 2014 this rate decreased to 74,91%. The target set by management is 80%. Therefore, job satisfaction rate of RSMUâs employees has not reached the target. The aim of this study is to analyze the influence of leadership, employee involvement, and continuous improvement principle implementationtowards the job satisfaction of RSMUâs employees. This study used observational method with cross sectional design. The data was obtained through questionnaire with simple random sampling involving 90 employees as the sample of the research. The next step is analyzing the data analytically by using logistic regression test univariate (Î±=0,05) to examine the influence of leadership, employee involvement, and continuous improvement principle implementation towards the employeeâs job satisfaction. The test result indicates that there are influences of two principles implementation towards the employeeâs job satisfaction. Those principles, on the one hand, are leadership (sig=0,002) and continuous improvement (sig=0,006). On the other hand, the implementation of employee involvement does not affect the job satisfaction.Keywords :Employee job satisfaction, leadership, employee involvement, continuous improvement